2001
DOI: 10.1148/radiol.2203010070
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Carcinomatosis: Image-guided Peritoneal Core Biopsy for Tumor Type and Patient Care

Abstract: Image-guided peritoneal core biopsy with hematoxylin-eosin analysis supplemented with immunohistochemical analysis is a simple, safe, and accurate technique for providing site-specific diagnoses in women with undiagnosed peritoneal carcinomatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 14 publications
2
32
0
2
Order By: Relevance
“…The authors reported only one complication of a rectus sheath haematoma. A second earlier study by the same institution [10] involved 35 female patients, 31 of whom had CT-guided biopsy using an 18-gauge cutting needle. The authors reported a high accuracy rate of 92%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported only one complication of a rectus sheath haematoma. A second earlier study by the same institution [10] involved 35 female patients, 31 of whom had CT-guided biopsy using an 18-gauge cutting needle. The authors reported a high accuracy rate of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few publications on the use of imageguided percutaneous biopsy to determine management in advanced ovarian carcinoma [9][10][11], with most studies describing results of computed tomography (CT)-guided percutaneous biopsy in patients with peritoneal carcinomatosis. The aims of the current study are: (1) to report the accuracy of image-guided percutaneous biopsy in patients with suspected ovarian cancer prior to start of neo-adjuvant chemotherapy; (2) to evaluate if large-gauge (14-16 swg) biopsy needles are as safe as small-gauge (18-20 swg) needles, and (3) to compare the accuracy and safety of USguided biopsy with CT-guided biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the immunohistochemical marker profi le was unlike that of primary peritoneal cancer. 15 Therefore, ectopic peritoneal mesothelium was probably not the origin of the carcinoma. Because S-1 has been used effectively in the treatment of pancreatic, gastric, or colorectal cancer, we gave S-1 as an adjuvant chemotherapy agent to this patient based on the aforementioned immunohistochemical fi ndings.…”
Section: Discussionmentioning
confidence: 99%
“…14 In patients with indeterminate clinical and radiological findings of benign and malignant peritoneal masses, imageguided peritoneal core biopsy can be safely done for determining the tumor type. 20 In recent published papers, color Doppler US has been reported to be useful in differentiating malignancies from benign tumors and predicting and assessing the chemotherapy response of tumors. Quantitative flow parameters, RI and PI, measured from tumor vessels were compared in benign and malignant conditions.…”
Section: Discussionmentioning
confidence: 99%